2015
DOI: 10.1002/rcs.1640
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of robotically‐assisted laparoscopy, laparoscopy and laparotomy: a comparison

Abstract: Our results provide clinicians, administrators and policy-makers with knowledge of the environmental impact of their decisions to facilitate adoption of sustainable practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 19 publications
1
62
0
1
Order By: Relevance
“…With regard to CO 2 production and energy consumption, Woods et al investigated 150 procedures (laparotomy, conventional laparoscopy and robot-assisted laparoscopy) demonstrating a consumption of 40.3 kg CO 2 /patient for robotassisted surgery. This was 38% higher than CO 2 production caused by conventional laparoscopy and 77% higher than that of open surgery [27].…”
Section: Discussionmentioning
confidence: 66%
“…With regard to CO 2 production and energy consumption, Woods et al investigated 150 procedures (laparotomy, conventional laparoscopy and robot-assisted laparoscopy) demonstrating a consumption of 40.3 kg CO 2 /patient for robotassisted surgery. This was 38% higher than CO 2 production caused by conventional laparoscopy and 77% higher than that of open surgery [27].…”
Section: Discussionmentioning
confidence: 66%
“…Following application of the inclusion and exclusion criteria, eight studies were found to be eligible. (7,26,27,(31)(32)(33)(34)(35) Of these, four were conducted exclusively in the US, (7,31,33,35) two in the UK, (27,32), one in Chile (26), and one in India (Table 1). (34) Variation in methods for carbon footprinting (Table 1)…”
Section: Study Selectionmentioning
confidence: 99%
“…Unlike other specialties, the environmental footprint of both of these procedures have been analysed in prior studies. 19,20,28,29 Additionally, ObGyn physicians work with, in general, patients who are highly motivated to improve environmental conditions.…”
Section: Introductionmentioning
confidence: 99%